Studi Kolam Retensi Sebagai Upaya Pengendalian Banjir Sungai Bruno Desa Sidomulyo Kecamatan Semen Kabupaten Kediri - Ardinata Ardinata; Yosef Cahyo Setianto Poernomo; Agata Iwan Candra (Faculty of Engineering, Kadiri University, 2020)
Retention ponds function to fill time and can be combined with a pump or floodgates to cope with flooding. This study aims to determine the flood discharge that the Bruno River cannot accommodate. The method used is data from the research location and literature review of previous studies. Namely Hydrological Analysis of rainfall data for 10 years taken from the Kanyoran station. Until calculating the flood discharge plan with the Rational method. The Rational Method is one of the common methods used to estimate the peak flow rate. Results for a 50 year return period, get an excess of flood discharge of 64,363 m3 / s, duration of rain (t) 3.2 hours and a minimum storage volume of 378 580.32 m3 . Retention pond with dimensions plan K1 p = 300m, l = 130m, t = 2m, and K2 p = 300m, l = 125m, t = 2m. Kolam Retensi berfungsi untuk menampung air sementara waktu dan dapat dikombinasikan dengan pompa atau pintu air untuk menanggulangi banjir. Penelitian ini bertujuan untuk mengetahui debit banjir yang tidak dapat ditampung oleh sungai Bruno. Penelitian ini menggunakan Analisis Hidrologi terhadap data curah hujan selama 10 tahun yang diambil dari stasiun Kanyoran. Hingga menghitung debit banjir rencana dengan metode Rasional. Metode Rasional adalah Salah satu metode umum yang di gunakan untuk memperkirakan laju aliran puncak Hasil untuk kala ulang 50 tahun, didapatkan kelebihan debit banjir sebesar 64,363 m3/dtk, lama hujan (t) 3,2 jam dan volume tampungan minimal sebesar 378 580,32 m3 . Kolam Retensi direncanakan dengan dimensi K1 p = 300m, l = 130m, t = 2m, dan K2 p = 300m, l = 125m, t = 2m.